KEANEKARAGAMAN JENIS AMPIBI (Ordo Anura) DALAM KAWASAN HUTAN LINDUNG GUNUNG AMBAWANG KECAMATAN KUBU KABUPATEN KUBU RAYA - Novita Sari, Indah; Nurdjali, Bachrun; anto, Eri (Universitas Tanjungpura, 2014)
The research aimed to know is for determine diversity of amphibians species as data in the amphibians conservation developments in the Gunung Ambawang Protected Forest Areas, Kubu District, Kubu Raya Regency. The method used in this research is a Visual Encounter Survey (VES) or Visual Encounter Survey combined with Transect System. The numbers of species found 11 species from 4 familys, with a total of 77 individuals consisted 3 individuals of Limnonectes malesianus, 4 individuals Rhacophorus pardalis, 18 individuals Limnonectes kuhlii, 4 individuals Hylarana baramica, 25 individuals Ansonia spinulifer, 4 individuals Fejevarya limnocharis, 1 individual Pseudobufo subasper, 6 individuals Hylarana chalconota, 4 individuals Hylarana erythraea, 3 individuals Bufo melanosticus and 5 individuals Hylarana nicobariensis. Highest diversity Index on aquatic habitats with the value = 0,8855, than for the transect level, highest diversity index on transect 1 with the value = 0,8846. Evenness index for each observation transect is not too different, the highest value on transect 4 (e = 0.6875), and the lowest on transect 6 (e = 0.5000). Similarity index between the aquatic habitat and terrestrial habitat by 84,21 % or more of most species are found in both habitats are almost same. Ansonia spinuliferis the greatest chance encounter with the value 0.6204 individuals per hour and the smallest chance encounter is Pseudobufo subasperwith the value 0.0278 individuals per hour with the total of chance encounter 1.9074 individuals per hour. Keywords: Amphibians, Anura, Gunung Ambawang, Diversity